THE INTERRELATION BETWEEN MAUVAISE FOI AND RADICAL FREEDOM IN ZOULFA KATOUH'S AS LONG AS THE LEMON TREES GROW - Nugrahani, Ananda Meira; Imas Istiani, (Elite : English and Literature Journal, 2025)
This research aims to offer a philosophical character analysis by exploring the interrelation of the existential dilemma experienced by Salama and Kenan in Zoulfa Katouh's novel As Long as the Lemon Trees Grow. The research adopts Jean-Paul Sartre's existentialist framework, particularly the concepts of Mauvaise Foi (Bad Faith) and Radical Freedom, which are central to understanding the characters’ internal conflicts. Salama and Kenan are both torn in a situation of Mauvaise Foi or a condition where they are struggling against the inner turmoil between remaining to stay in their homeland out of duty and patriotism or fleeing to seek refugee for the sake of future and safety. Initially, they deceived themselves by feeling that they had no choice but to stay, when in fact they had an alternative option to leave. This is particularly aligned with the concept of Mauvaise Foi, in which individuals reject the truth about themselves and are trapped in an illusion that they have imposed. Radical Freedom, on the other hand, is the decision and form of manifestation they finally make with full awareness and responsibility for their freedom. These two existential concepts dynamically interact to shape the character’s existential journey throughout the novel. By analyzing how these two existential concepts operate and interact within the narrative, this study highlights the characters’ philosophical journey and contributes to the broader discussion of existentialism in war literature.